2012
DOI: 10.1590/s0102-695x2012005000050
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ulcer activity of Synadenium grantii latex

Abstract: Synadenium grantii Hook f., Euphorbiaceae, is popularly known as leitosinha or janaúba. The diluted latex (18 drops/L of water) is commonly used in the south of Brazil to treat gastric disturbances. This study evaluated phytochemical screening and toxicity using Artemia salina Leach of crude bark extract and also latex. The toxicity and the anti-ulcer activity of S. grantii latex were also tested in rats. Phytochemical results showed presence of tannins, terpenes, unsaponificable substances, coumarins and anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 38 publications
4
29
1
Order By: Relevance
“…There was no evidence of damage to liver tissue from use of the garrafada of Synadenium grantii. This result is in agreement with results obtained by Costa et al (2012), who evaluated hepatic biochemical parameters in rats treated with garrafada of Synadenium grantii and found no significant difference between the treated group and the control group; however, these same authors reported that in the highest concentrations of the latex, significant changes in biochemical parameters were found.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There was no evidence of damage to liver tissue from use of the garrafada of Synadenium grantii. This result is in agreement with results obtained by Costa et al (2012), who evaluated hepatic biochemical parameters in rats treated with garrafada of Synadenium grantii and found no significant difference between the treated group and the control group; however, these same authors reported that in the highest concentrations of the latex, significant changes in biochemical parameters were found.…”
Section: Discussionsupporting
confidence: 92%
“…Even more relevant to the subject of the present research is the fact that the toxicity of the Synadenium grantii species has also been reported, evaluated by Artemia salina, presenting an LD50 value of 26.58 μg/mL for latex from the plant (Costa et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In folk medicine the latex of Synadenium grantii Hook f. to treat neoplasic diseases and gastric disorders such as peptic ulcers and gastritis inflammatory [12]. Moreover, studies in animals showed that the latex extracts of Synadenium grantii Hook f. has anti-ulcer activity without causing toxicity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies in animals showed that the latex extracts of Synadenium grantii Hook f. has anti-ulcer activity without causing toxicity [12]. The cytotoxicity as well as the antiparasitic activity of the CHCl 3 extract of Synadenium grantii Hook f. leaves was performed and proved to be active [13].…”
Section: Introductionmentioning
confidence: 99%